Amygdala atrophy is prominent in early Alzheimer's disease and relates to symptom severity - Poulin, Stéphane P.; Dautoff, Rebecca; Morris, John C.; Barrett, Lisa Feldman; Dickerson, Bradford C. (Psychiatry research. Neuroimaging, 2011)
Despite numerous studies on the role of medial temporal lobe structures in Alzheimer's disease (AD), the magnitude and clinical significance of amygdala atrophy have been relatively sparsely investigated. In this study, we used magnetic resonance imaging (MRI) to compare the level of amygdala atrophy to that of the hippocampus in very mild and mild AD subjects in two large samples (Sample 1 n = 90; Sample 2 n = 174). Using a series of linear regression analyses, we investigated whether amygdala atrophy is related to global cognitive functioning (Clinical Dementia Rating Sum of Boxes: CDR-SB; Mini Mental State Examination: MMSE) and neuropsychiatric status. Results indicated that amygdala atrophy was comparable to hippocampal atrophy in both samples. MMSE and CDR-SB were strongly related to amygdala atrophy, with amygdala atrophy predicting MMSE scores as well as hippocampal atrophy, but predicting CDR-SB scores less robustly. Amygdala atrophy was related to aberrant motor behavior, with potential relationships to anxiety and irritability. These results suggest that the magnitude of amygdala atrophy is comparable to that of the hippocampus in the earliest clinical stages of AD, and is related to global illness severity. There also appear to be specific relationships between the level of amygdala atrophy and neuropsychiatric symptoms that deserve further investigation.